2010
DOI: 10.1038/npp.2010.56
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tasking and Working Memory in Alcoholism: Relation to Frontocerebellar Circuitry

Abstract: Controversy exists regarding the role of cerebellar systems in cognition and whether working memory compromise commonly marking alcoholism can be explained by compromise of nodes of corticocerebellar circuitry. We tested 17 alcoholics and 31 age-matched controls with dual-task, working memory paradigms. Interference tasks competed with verbal and spatial working memory tasks using low (three item) or high (six item) memory loads. Participants also underwent structural MRI to obtain volumes of nodes of the fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 69 publications
8
47
0
1
Order By: Relevance
“…Some researchers have suggested that the lack of detectable deficits in these seemingly spared domains could be due to compensatory recruitment of alternative brain regions to facilitate cognitive processes (Sullivan and Pfefferbaum, 2005; Oscar-Berman and Marinkovic, 2007; Chanraud et al, 2013). In support of this notion, fMRI studies have demonstrated altered patterns of neural activation among alcoholics, with reduced activity in some regions (Chanraud et al, 2010; Chanraud et al, 2011), but simultaneous increases in activity in others (Pfefferbaum et al, 2001a; Desmond et al, 2003; Chanraud-Guillermo et al, 2009; Chanraud et al, 2013). As such, it can be difficult to distinguish between functions that have been truly spared and those that appear unimpaired due to compensatory mechanisms or other recovery of function.…”
Section: The Impaired the Spared And The Recoveredmentioning
confidence: 87%
“…Some researchers have suggested that the lack of detectable deficits in these seemingly spared domains could be due to compensatory recruitment of alternative brain regions to facilitate cognitive processes (Sullivan and Pfefferbaum, 2005; Oscar-Berman and Marinkovic, 2007; Chanraud et al, 2013). In support of this notion, fMRI studies have demonstrated altered patterns of neural activation among alcoholics, with reduced activity in some regions (Chanraud et al, 2010; Chanraud et al, 2011), but simultaneous increases in activity in others (Pfefferbaum et al, 2001a; Desmond et al, 2003; Chanraud-Guillermo et al, 2009; Chanraud et al, 2013). As such, it can be difficult to distinguish between functions that have been truly spared and those that appear unimpaired due to compensatory mechanisms or other recovery of function.…”
Section: The Impaired the Spared And The Recoveredmentioning
confidence: 87%
“…Additionally, there is data to suggest a functional topography of the cerebellum, with posterior regions preferentially involved in cognitive processes whereas anterior portions of the cerebellum support motor functions [56]. Previous work comparing 17 alcohol-dependent individuals and 31 controls has revealed performance deficits in visuospatial working memory tasks that are related to structural differences in left cerebellar Crus I, though differences in verbal working memory functioning did not appear to be impaired in alcohol-dependent individuals [9]. In a study of 15 patients with spinocerebellar ataxia, verbal working memory deficits were found using the WAIS subtests (Forward and Backward Digit Span and Letter Number Sequencing) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies have demonstrated that individuals with posterior cerebellar lesions consistently display working memory deficits [4, 7, 8], whereas damage to other cerebellar regions does not appear to affect working memory [7]. Positive correlations between posterior cerebellar lobe volume and working memory performance have been reported [911] along with greater BOLD activation during working memory task performance [1214]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when compared to controls in task performance, alcoholic patients have shown spontaneous, compensatory recruitment of additional brain networks like fronto-cerebellar and others (Chanraud, Pitel, Rohlfing, Pfefferbaum & Sullivan, 2010;Chanraud, Pitel, Pfefferbaum & Sullivan, 2011;Parks et al, 2012;Camchong, Stenger & Fein 2012;Chanraud, Pitel, Muller-Ohering, Pfefferbaum & Sullivan, 2013). Some of these compensatory strategies have been linked to the ability to sustain abstinence .…”
Section: Neurocognitive Rehabilitation In Alcohol Use Disordersmentioning
confidence: 99%